The Evaluation of the Relationship between the Use of Multi-Software and the Students’ Attitude towards Computers and Technology in Undergraduate Architectural Design Studio Education - Agirbas, Asli (Design and Technology Education: An International Journal, 2019)
Different computer programs used in the architectural design process serve different purposes. However, the number of computer programs used is increasing at a rate that designers find it difficult to adapt to. Accordingly, the possibility arises to use more than one computer program during the architectural design process, and it is important to make the correct choice of which ones are most appropriate to use. This is also true for undergraduate students of architecture, and hence a pilot study was made, which focused on the use of multi-software within the scope of the architectural design studio. The relationship between the students' use of multi software and their attitude toward computer and technology was evaluated statistically, by means of Pearson product moment correlations. The results showed that the attitude of the students toward computers and technology influences how they use multi-software.